A study on the fragility modeling of mid-rise tunnel form RC buildings for Turkey - Özen, Uğur. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2021., 2021)
The mid-rise tunnel form RC buildings in metropolitan cities in Turkey and their dynamic behavior against earthquake action are investigated by deriving a representative model. First of all, the compiled blueprints of the tunnel form RC building inventory are categorized into four different groups and their fundamental features are studied statistically. The first group, which is the focus of this study represents general features of mid-rise tunnel form buildings in Turkey. Secondly, the nonlinear structural model of this building is developed based on the code requirements and guidelines to perform push-pull and pushover analysis for obtaining its simplified SDOF version in the MSc thesis of Curic (2021). The results of these two theses will complete and augment each other in a near-future collaborative work. Then, the ground motions selected and scaled to the target conditional-response spectra developed in Curic (2021) are used together with the provisions in the 2018 Turkish Building Earthquake code, 2004 Eurocode, and 2017 ASCE code to assess the structural performance of the model building (through damage states) for developing fragility curves. The observations from this study show that the performance of mid-rise tunnel form buildings can be called as satisfactory under the requirements dictated by the national and international standards. Another observation is that different engineering demand parameters give different performance assessment results. Hence, novel global and local performance demand parameters should be investigated by studying other categories (mid- and high-rise) tunnel form buildings. The variabilities in (1) engineering demand parameters, (2) structural properties such as story number, types of vertical elements, and mathematical model, and (3) the definition of limit states in both local and global performance levels have a significant effect on the fragility curves. These variabilities are taken into account for performance based assessment.
Keywords: Buildings -- Earthquake effects -- Turkey.; Buildings, Reinforced concrete -- Turkey -- Earthquake effects.